PERBANDINGAN PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE (5E) DAN TWO STAY TWO STRAY - Erva Rosa Prima Gayatri; Amrul Bahar; Dewi Handayani (University of Bengkulu, 2017)
The purpose of this research is to know the difference of students' chemistry learning result between experiment 1 class which applied learning cycle model (5E) with experiment 2 class that apply two stay two stray learning model on acid acid base material in class XI IPA in SMA Plus Negeri 7 Bengkulu City. Research conducted is a research with the type of quasi experiment. Chemical learning result data obtained from pretest value and posttest value where the average value of improvement of cognitive learning result for experiment class 1 is 47,78. And the average value of cognitive learning improvement for experiment class 2 is 54.875. With testing the hypothesis using t test with significant level (? = 0,01), then got value for titung equal to 2,60 and for ttable got value equal to 2,380. The results showed that there were significant differences in learning outcomes between classes that applied learning cycle model (5E) with classes that applied the two stay two stray learning model.